A Generalized Meir-Keeler-Type Contraction on Partial Metric Spaces - Hassen Aydi; Erdal Karapınar; Shahram Rezapour (Abstract and Applied Analysis)
We introduce a generalization of the Meir-Keeler-type contractions, referred to as generalized Meir-Keeler-type contractions, over partial metric spaces. Moreover, we show that every orbitally continuous generalized Meir-Keeler-type contraction has a fixed point on a 0-complete partial metric space.